PENETRASI SOSIAL DALAM HUBUNGAN ASMARA PENGGUNA APLIKASI DISCORD : STUDI FENOMENOLOGI PADA SERVER GANG SEBELAH - Mutiara Adawiyazzahra, (2023)
Discord is an audio and community-based social media platform with full features compared to other social media platforms. Discord is used by its users to find friends and partners, one of which is due to the presence of the Covid-19 pandemic which has hampered people from communicating and forming face-to-face relationships. Gang Sebelah server as an online community server is a place for gathering, interacting, and forming relationships. This study aims to determine the social penetration process of Discord application users. Phenomenology as a method and qualitative approach is used in this study. The data collection method was carried out through in-depth interviews online using a zoom meeting with six informants members of Gang Sebelah server. The results of the study show the development of interpersonal relationships based on the stages of social penetration theory, which is orientation, affective exploratory exchanges, affective exchanges, and stable exchanges. The process of developing face-to-face and virtual interpersonal relationships goes through the same stages, the difference is that the time that tends to be fast in the virtual communication process on Discord is influenced by the high intensity of communication, and this intensity also affects more and more rapid self-disclosure. In the process of developing relationships on Discord, the high intensity that continues to occur from the close beginning to this stage actually causes a decrease in communication in intimate relationships, even so intimacy is maintained by maintaining each other's presence so that the relationship does not enter the termination stage. Only one couple can reach the stable exchange stage, because the other couple have not yet reached the deepest self-disclosure.